Comment on "spaser action, loss compensation, and stability in plasmonic systems with gain" - Wuestner, S.; Pusch, A.; K. L. Tsakmakidis; Hamm, J.M.; Hess, O. (Physical Review Letters, 2011)
A Comment on the Letter by Mark I. Stockman, Phys. Rev. Lett.PRLTAO0031-9007 106, 156802 (2011)10.1103/PhysRevLett.106.156802. The author of the Letter offers a Reply. © 2011 American Physical Society.
cited By 10